Depression, anxiety and worry in young Pacific adults in New Zealand during the COVID-19 pandemic. (May 2023) - Siegert, Richard J; Narayanan, Ajit; Dipnall, Joanna; Gossage, Lisa; Wrapson, Wendy; Sumich, Alexander; Merien, Fabrice; Berk, Michael; Paterson, Janis; Tautolo, El-Shadan
Objective: To measure symptoms of anxiety, depression and hopelessness in a sample of young Pacific adults living in Auckland, New Zealand during the 2020/2021 COVID-19 pandemic and identify protective factors. Methods: Participants were 267 Pacific adults (58% female) who completed a survey online. Analyses included descriptive statistics, correlations, linear regression and symptom network analysis. Results: Around 25% of the sample scored in the range for moderate to severe anxiety and 10% for moderate to severe depression on standard measures. Almost 40% indicated that they found the first lockdown very stressful and 55% noted that some members of their family found it stressful. Only 16% worried about COVID-19 and their future quite a bit or constantly, while another 25% worried sometimes . Self-compassion and Pacific Identity had moderate, negative correlations, and Worry about COVID-19 had weak positive correlations, with anxiety, depression, hopelessness and perceived stress. Conclusion: These results suggest that, while the prevalence of depression and anxiety are quite high among this population, fostering ethnic identity and self-compassion in Pacific children and adolescents might protect against developing depression and anxiety.